Penerapan Sistem Close Access pada Layanan Sirkulasi di Perpustakaan Politeknik Pertanian UNAND Payakumbuh - Fajri, Ilkhamul; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
This topics has goal for  to describe how the system of sirculation service that use library of agricultural polythecnic unand, payakumbuh and  to describe the problems that we get in the  service. The collecting of data uses live communicatin technic with a personal of library and catch it. Follow this analysis of data can conclude about (1) . Library of agricultural polytechnic unand use close acces system in this sirculation service (2). The problems that we get to use close acces system in this sirculation in library of agricultural polythecnic unand, payakumbuh is increase the personal of library, they get off to give service in library and haven’t online katalog. Keywords: closse acces; sirculation service